LncRNA MALAT1 Regulates the Progression and Cisplatin Resistance of Ovarian Cancer Cells via Modulating miR-1271-5p/E2F5 Axis [Retraction] - Wang Y; Wang X; Han L; Hu D (Cancer Management and Research, 2022)
Wang Y, Wang X, Han L, Hu D. Cancer Manag Res. 2020;12:9999–10010. At the authors request, the Editor and Publisher of Cancer Management and Research wish to retract the published article. The authors raised concerns over similarities between the flow cytometry data provided in Figures 2, 4 and 7 and indicated that it may have been fabricated. In addition, the authors advised that the cell migration and invasion data also provided in Figures 2, 4 and 7 was unreliable. The authors were unable to provide original data for their study and could not verify the reported findings. The Editor agreed with the authors decision to retract the article. We have been informed in our decision-making by our policy on publishing ethics and integrity and the COPE guidelines on retractions. The retracted article will remain online to maintain the scholarly record, but it will be digitally watermarked on each page as “Retracted”.